Pengaruh Frekuensi Pemberian Pupuk Organik Cair dan Takaran Biochar terhadap Pertumbuhan dan Hasil Sawi Pakcoy (Brassica rappa L.) - Asep Iksan Gumelar; Yunus Kornelis To (Fakultas Pertanian, Universitas Timor, 2021)
This study aims to determine the effect of the frequency of application of liquid fertilizer and biochar on the growth and yield of pakcoy plants and to obtain the frequency of application of liquid fertilizer that is appropriate for the growth and yield of pakcoy plants. This research has been carried out for one planting season from August to September 2020, on Mr Marten Kaet's land, located in Benpasi Village, Kefamenanu City District, North Central Timor Regency (TTU), East Nusa Tenggara Province (NTT). Using a 2 Factorial Randomized Block Design (RBD), namely: The first factor: Biochar which consists of 3 levels, namely: Biochar 10 t / ha, Biochar 20 t / ha, Biochar 30 t /Ha. The second factor is the frequency of watering liquid fertilizer which consists of 4 levels of treatment, namely: 5ml / liter of water: 2 times a week, 5ml / liter of water: 1 time a week, 10 ml / liter of water : 2 times a week, 10 ml / liter of water: once a week. So there are 12 treatment combinations, namely: B1F1, B1F2, B1F3, B1F4, B2F1, B2F2, B2F3, B2F4, B3F1, B3F2, B3F3, B3F4which were repeated as many 3 times so that there are 36 experimental units. The results showed no interaction and significant differences between the treatment of biochar dose and POC watering frequency on the growth and yield of mustard greens (Brassica rappa L.). But there was a significant difference in the leaf area parameters. The results showed that the treatment of 30 t/ha biochar dose and 5 ml / L POC watering frequency was able to increase the growth and yield of mustard greens (Brassica rappa L.). This was indicated by the highest value given both on environmental parameters, growth and the result.